2019
DOI: 10.1177/1179554919829500
|View full text |Cite
|
Sign up to set email alerts
|

Access to Palliative Care for Cancer Patients Living in a Northern and Rural Environment in Ontario, Canada: The Effects of Geographic Region and Rurality on End-of-Life Care in a Population-Based Decedent Cancer Cohort

Abstract: Background:Access to palliative care has been associated with improving quality of life and reducing the use of potentially aggressive end-of-life care. However, many challenges and barriers exist in providing palliative care to residents in northern and rural settings in Ontario, Canada.Aim:The purpose of this study was to examine access to palliative care and associations with the use of end-of-life care in a decedent cohort of northern and southern, rural and urban, residents.Design:Using linked administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Another study also found rural residency to increase the rate ratio of the total number of ED visits after controlling for patient characteristics and the effect of continuity of care with a family physician (OR 1.29, 95% CI, 1.21–1.37) [ 10 ]. Similar results were found in four studies where higher rates of ED visits were reported in the last 30 days of life [ 29 , 35 ] among cancer decedents living in rural areas compared to urban areas with rates reducing with narrower time periods to death [ 35 ] such as the last two weeks of life [ 9 , 27 ].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Another study also found rural residency to increase the rate ratio of the total number of ED visits after controlling for patient characteristics and the effect of continuity of care with a family physician (OR 1.29, 95% CI, 1.21–1.37) [ 10 ]. Similar results were found in four studies where higher rates of ED visits were reported in the last 30 days of life [ 29 , 35 ] among cancer decedents living in rural areas compared to urban areas with rates reducing with narrower time periods to death [ 35 ] such as the last two weeks of life [ 9 , 27 ].…”
Section: Resultssupporting
confidence: 85%
“…The most common index used to measure rurality was objective measures of population concentration derived from 2006 Canadian Census of the Populations and the Registered Persons Database (RPD). This was assessed in four studies (17%) [ 9 , 11 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of concern for collaborating health professionals, consumers and policy makers is how well rural GPs are providing palliative and EOL care, and what can be done to maximise the effectiveness of their care for people at the EOL and their informal carers in Australia (Ding, Saunders, Cook, & Johnson, 2019) and other countries (Chukwusa et al., 2019; Conlon et al., 2019; Isaacson & Lynch, 2017; Leng, Jing, Nicholas, & Wang, 2019; Warraich et al., 2019). Prior to the development of interventions to support GPs and consumers, it is necessary to identify the attributes of EOL care and current gaps in service delivery within rural settings.…”
Section: Introductionmentioning
confidence: 99%